Amitriptyline: prophylactic model modulates dss-colitis in mice - Namazu, L. B.; Calefi, A. S.; Gimenes, D.; Oliveira, R.; Cohn, D. W.; Lima, A. P. N.; Vitoretti, L. B.; Drewes, C. C.; Amaya, J. E. O.; Borsoi, A.; Reis-Silva, T. M.; Massoco, C. O.; et al. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2015)
Introduction: inflammatory bowel disease (IBD) in humans is a chronic disease of complex ethiology that manifests as Crohn’s disease (CD) or ulcerative colitis (UC). It involves an exacerbated immune reaction to the gut microbiota. The nervous system interacts with immunity in the gut in a bidirectional fashion. Inflammation is modulated by neural activity and may lead to emotional and psychological changes. Amitriptyline (AMT) is a commonly used antidepressant with known anti-inflammatory activities.Objective: It was hypothesized that antidepressants like amitriptyline could be considered as a prophilatic treatment and attenuation of development of IBD in mice.Material and Methods: C57BL/6 mices were housed in groups of five per cage with free access to food and water without treatment (Vehicle) or with Amitriptyline and Dextran Sulphate Sodium (AMT/DSS). The groups were Vehicle (1), Vehicle+DSS (2), Vehicle+DSS+AMT (3) and, Vehicle+AMT (4). The prophylactic model consisted of the AMT (200 μg/ml) administration p.o. for 14 days on animals in the groups 3 and 4. After 14 days animals in groups 2 and 3 received DSS (3,5%) for 5 days. The tissues were collected in the 19th experimental day. The circulating and colonic (proximal and distal) inflammatory cytokines (IL-6, TNF-alpha and IL-1 β) were quantified, and the neutrophilic inflammatory response was assessed by the myeloperoxidase (MPO) activity on colon (proximal and distal).This project was approved by the Ethics Committee on animal use of the School of Veterinary Medicine and Animal Science- USP (Protocol 2999/2013).Results: the AMT prophylactic treatment was able to prevent the animal weight loss by the DSS induced colitis. Circulating IL-6 and TNF-alpha were reduced by the prophylactic AMT treatment associated with the decreased MPO activity in the proximal colon.Conclusion: the reduction in the DSS-colitis in mice induced by the AMT treatment, may lead a possible use of amitriptyline to reduce the IBD clinical signs in humans.